Tematyka archeologiczna w leszczyńskim „Przyjaciel Ludu" - Jędrzejczyk, Konrad (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
In the mid-19th century archaeology on the teritory of the Prussian partition had more convenient development conditions than on the territories of other partitions. The past, which was often referred to, was to compensate for military failures. It seems that archaeology of those days became one of the instruments of the fight for independence. In a process of antiquity interest development a weekly magazine „Przyjaciel Ludu” („The Friend of the People”) played a significant role. It was issued in 1834-1849 in Leszno. The periodical, displayed close connections with a postulate of organic work, presented its readers a wide thematic extent. Most of the articles published in the paper were devoted to history; articles within the scope of ethnography and literature constituted next considerable part. „Przyjaciel Ludu” also contained quite a lot of pieces of information on archaeological excavations and numerous notes or articles were sent to the editor by members of Towarzystwo Zbieraczów Starożytności Krajowych (the National Antiquities Collectors Society). „Przyjaciel Ludu" as one of the first Polish papers raised archaeological problems to a large extent and, at the same time, it played a considerable role in the development of Polish modern archaeology.